Effects of Prometryn Exposure on Hepatopancreas Oxidative Stress and Intestinal Flora in Eriocheir sinensis (Crustacea: Decapoda) - Peng Huang; Liping Cao; Jinliang Du; Jiancao Gao; Yuning Zhang; Yi Sun; Quanjie Li; Zhijuan Nie; Gangchun Xu (MDPI AG, 2023)
There is growing evidence that long-term exposure to prometryn (a widely used herbicide) can induce toxicity in bony fish and shrimp. Our previous study demonstrated its 96 h acute toxicity on the crab Eriocheir sinensis. However, studies on whether longer exposure to prometryn with a lower dose induces toxicity in E. sinensis are scarce. Therefore, we conducted a 20 d exposure experiment to investigate its effects on the hepatopancreas and intestine of E. sinensi. Prometryn reduce the activities of antioxidant enzymes, increase the level of lipid peroxidation and cause oxidative stress. Moreover, long-term exposure resulted in immune and detoxification fatigue, while short-term exposure to prometryn could upregulate the expression of genes related to immunity, inflammation and detoxification. Prometryn altered the morphological structure of the hepatopancreas (swollen lumen) and intestine (shorter intestinal villi, thinner muscle layer and thicker peritrophic membrane). In addition, prometryn changed the species composition of the intestinal flora. In particular, Bacteroidota and Proteobacteria showed a dose-dependent decrease accompanied by a dose-dependent increase in Firmicutes at the phylum level. At the genus level, all exposure groups significantly increased the abundance of Zoogloea and a Firmicutes bacterium ZOR0006, but decreased Shewanella abundance. Interestingly, Pearson correlation analysis indicated a potential association between differential flora and hepatopancreatic disorder. Phenotypic abundance analysis indicated that changes in the gut flora decreased the intestinal organ's resistance to stress and increased the potential for opportunistic infection. In summary, our research provides new insights into the prevention and defense strategies in response to external adverse environments and contributes to the sustainable development of E. sinensis culture.